2011
DOI: 10.3109/09638237.2011.562263
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of involuntary admission and risk of subsequent readmission at one-year follow-up: The influence of insight and recovery style

Abstract: Peoples' perception of the necessity of their involuntary admissions is not stable over time and risk of involuntary readmission is associated with recovery style.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…In around half of the papers the analysis considered readmission to all possible hospitals. In three cases, readmission was restricted to involuntary readmission in the context of involuntary index admission or detention [14, 41, 42] while in other three [33, 34, 43] involuntary readmitted patients were explicitly excluded from the analysis. In one paper readmission specific for self-harm was considered [44].…”
Section: Resultsmentioning
confidence: 99%
“…In around half of the papers the analysis considered readmission to all possible hospitals. In three cases, readmission was restricted to involuntary readmission in the context of involuntary index admission or detention [14, 41, 42] while in other three [33, 34, 43] involuntary readmitted patients were explicitly excluded from the analysis. In one paper readmission specific for self-harm was considered [44].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a large proportion of the participants had more than one admission (65.2%) and were assigned a diagnosis of non-affective psychotic disorder (69.6%); both of which have been reported to inform persistently negative attitudes towards involuntary admission and care O'Donoghue et al 2010O'Donoghue et al , 2011aO'Donoghue et al , 2011bO'Donoghue et al , 2016Priebe et al 2010;Smith et al 2014). Previous evidence also suggests that service users who are subject to coercive measures tend to hold negative attitudes about the care they received O'Donoghue et al 2010O'Donoghue et al , 2011aO'Donoghue et al , 2011bO'Donoghue et al , 2016Priebe et al 2010;Smith et al 2014). Participants in this study also reported feeling coerced in other aspects of their admission, described elsewhere (Murphy et al in press), and this may have impacted on their appraisals of the MHT.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly significant as only two of the service users involved in our study had their admission order revoked by the tribunal. To date, research investigating the factors influencing service users' attitudes towards the MHT process is sparse, hence future research is needed to identify the relevant demographic and clinical variables, such as those found to influence service users' attitudes towards involuntary admission in other studies O'Donoghue et al 2010O'Donoghue et al , 2011aO'Donoghue et al , 2011bO'Donoghue et al , 2016Priebe et al 2010;Smith et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that before discharge, 72% of service users perceived that their involuntary admission had been necessary (O'Donoghue et al 2010) and this reduced to 60% after 1 year (O'Donoghue et al 2011b). In the year following discharge, nearly two-thirds of service users engaged with their treating team and 43% were readmitted within 1 year, half of which, were involuntary (O'Donoghue et al 2011b). A large study had been conducted in the United Kingdom at a similar time and this found that only 40% of individuals admitted involuntarily perceived that their admission was justified (Priebe et al 2009).…”
Section: Introductionmentioning
confidence: 93%